INTERNATIONAL PRINCIPLES OF SUSTAINABLE DEVELOPMENT AND THE CHALLENGES TO ENVIRONMENTAL RIGHTS ENFORCEMENT IN NIGERIA - Murgan, Murtala Ganiyu A.; Ijaiya, Hakeem (Faculty of Law, Universitas Brawijaya, 2020)
Human existence in the environment with disregard for International Principles of Sustainable Environment has often led to overutilization of the nation?s natural and environmental resources, excessive gas flaring with consequences of global warming, flood, environmental degradation, desertification, water pollution, solid waste pollution, diseases and such conditions that violate human rights to a clean and healthy environment. Necessary International and National legal instruments as well agencies have also been put in place to overcome the above problems and enhance access to environmental justice for victims. However, it observed that these instruments could still not save mankind from the threat to Sustainable Development and environmental rights. This paper examines the challenges to the enforcement of environmental rights on sustainable development in Nigeria. With the qualitative content analysis doctrinal method, the study concludes that the enforcement of human rights on environmental pollution is very poor in Nigeria. The challenges to enforcement of Environmental rights on sustainable development goals also identify with useful recommendations.